Tellurium Compounds Prevent and Reverse Type-1 Diabetes in NOD Mice by Modulating α4β7 Integrin Activity, IL-1β, and T Regulatory Cells - Yossipof, Tom Eitan; Bazak, Ziva Roy; Kenigsbuch-Sredni, Dvora; Caspi, Rachel R.; Kalechman, Yona; Sredni, Benjamin (Frontiers in Immunology, 2019)
The study shows that treatment of NOD mice with either one of the two tellurium small molecules, AS101 [ammonium trichloro(dioxoethylene-o,o')tellurate]or SAS [octa-O-bis-(R,R)-tartarate ditellurane] could preserve beta cells function and mass. These beneficial effects were reflected in decreased incidence of diabetes, improved glucose clearance, preservation of body weight and increased survival. The normal glucose levels were associated with increased insulin levels, preservation of beta cell mass and increased islets size. Importantly, this protective activity could be demonstrated when the compounds were administered either at the early pre-diabetic phase with either no or initial insulitis, at the pre-diabetic stage with advanced insulitis, or even at the advanced, overtly diabetic stage. Our results imply that both tellurium compounds prevent migration of autoimmune lymphocytes to the pancreas, via inhibition of the alpha4beta7 integrin activity. Indeed, the decreased migration resulted in diminished extent of pancreatic islets damage both with respect to their size, beta cell function and caspase-3 activity, the hallmark of apoptosis. Most importantly, AS101 and SAS significantly elevated the number of T regulatory cells in the pancreas, thus potentially controlling the autoimmune process. We show that the compounds inhibit pancreatic caspase-1 activity followed by decreased levels of the inflammatory cytokines IL-1beta and IL-17 in the pancreas. These properties enable the compounds to increase the proportion of Tregs in the pancreatic lymph nodes. AS101 and SAS have been previously shown to regulate specific integrins by a unique redox mechanism. Our current results suggest that amelioration of disease in NOD mice by this unique mechanism is due to decreased infiltration of pancreatic islets combined with increased immune regulation, leading to decreased islets inflammation These activities suggest that these tellurium compounds that show remarkable lack of toxicity in clinical trials (AS101) or pre-clinical studies (SAS), may be suitable for the treatment of type-1 diabetes.